A critically discourse media analysis on the symbolic depiction of ?strong? female characters in selected Japanese ?shounen? animation shows - Enriquez, Rebekah Samantha E.; Sanchez, Samuelle Marionne C. (2023)
Media has a huge impact on the representation of groups and communities (Fu?rsich, 2010). In media, women are constantly underrepresented as their portrayals usually adhere to traditional gender roles, sexualization, and objectification (Behm-Morawitz & Pennell, 2013). Anime, or Japanese animation, is a form of media utilized for entertainment and to present the political and cultural agenda of Japan (Mizuno, 2007; Tengku Sabri & Ahmad, 2019). By understanding this, it is implied that anime as an entertainment medium should be analyzed. Regrettably, there is a scarcity of research in communication studies concerning the portrayal of female characters in Japanese anime. Therefore, this paper aims to analyze the depiction of female characters in anime using Feminist Critical Discourse Analysis, Theory of Symbolism, and Semiotic Analysis. The focus of the study is on "strong" female characters in selected Japanese shounen anime, which targets young male audiences. Preliminary data was gathered by watching various shows in this genre through legitimate streaming platforms. The visual and textual elements of the chosen female characters were examined for adherence to gender norms, objectification, and sexualization. While one character exhibited minimal issues in their depiction, the majority of the selected anime displayed problematic portrayals of their "strong" female characters. These findings emphasize the need for a critical analysis of how women are represented in anime, particularly in relation to gender stereotypesand objectification.
Thesis (BA Communication and Media Arts) -- University of the Philippines Mindanao, 2023